Constraints to fertilizer use in Nigeria: Insights from agricultural extension service - Banful, Afua Branoah; Nkonya, Ephraim M.; Oboh, Victor (International Food Policy Research Institute, 2010)
Fertilizer consumption rates in Nigeria remains among the lowest in the world despite decades of aggressive subsidization. The extension service in Nigeria has a double-edged impact on fertilizer use in the country; not only can their activities increase farmers' demand for fertilizer, but also the organizational framework of the service, Agricultural Development Programs, is the major source of fertilizer for farmers. To provide insights on the reasons for the low fertilizer use in Nigeria, this paper presents an analysis of the extension service as well as some perspectives of village extension agents. We find that the reach of the extension service is severely limited by low staff. The main technology transmitted is the use of improved seeds. Fertilizer technology is seldom transmitted and very rarely is irrigation taught. Furthermore, extension agents are found to have gaps in their knowledge of fertilizer technology. Extension agents routinely distribute agricultural inputs and many see their advisory role as secondary to this function. Extension agents identified the primary constraint to fertilizer use in Nigeria as the physical absence of the product at the time that it is needed, rather than lack of affordability or farmers' lack of knowledge about the benefits or the use of fertilizer.